Patterned formation of enolate functional groups on the graphene basal plane. Issue 45 (9th November 2018) - Cassidy, Andrew; Pedersen, Stine; Bluhm, Hendrik; Calisti, Valentin; Angot, Thierry; Salomon, Eric; Bisson, Régis; Hornekær, Liv
Abstract : O atoms selectivley bind at one type of site on the graphene basal plane, creating a long-range patterned distribution of graphene oxide nano-islands. Abstract : Chemical functionalization of graphene is one method pursued to engineer new properties into a graphene sheet. Graphene oxide is the most commonly used chemical derivative of graphene. Here we present experimental evidence for the formation of enolate moieties when oxygen atoms are added to the graphene basal plane. The exotic functional groups are stabilized by simultaneous bond formation between the graphene sheet and the underlying Ir(111) substrate. Scanning tunneling microscopy images demonstrate the patterned nature of C–O bond formation and X-ray photoelectron spectroscopy and high-resolution electron energy loss spectroscopy are used to characterize the enolate moiety. The results present a new mechanism for the formation of patterned graphene oxide and provide evidence of a functional group rarely considered for graphene oxide materials.